A study of primary caesarean section in multipara - Desai, Erika; Leuva, Harshraj; Leuva, Bakul; Kanani, Medha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Caesarean delivery is one of the most commonly performed operations today. Caesarean births have become safer. Primary caesarean section in a multipara means first caesarean section done in the patients who had delivered vaginally once or more. Mainly the baby and the placenta are responsible for caesarean section in multipara. Methods: It was a prospective randomized hospital based study of primary caesarean sections performed in multiparous patients at Dhiraj General Hospital at the Department of Obstetrics and Gynecology. In this study analysis of the cases in relation to different factors have been done. Results: Amongst the various indications for caesarean section in multipara, fetal distress (25.58%) and antepartum hemorrhage (22.09%) were with the highest incidence. Conclusion: Previous vaginal delivery gives the patient as well as her relatives a false sense of security. There are many cases where a caesarean becomes mandatory for her. The fact that a multipara has had one or more vaginal deliveries should be regarded as an optimistic historical fact, not as diagnostic-criteria for spontaneous delivery of the pregnancy at hand.